The development of ECVET in Europe - (:unkn) unknown (Publications Office of the European Union, 2010)
"The first Cedefop overview of the development of a European credit system for vocational education and training (ECVET) confirms the uptake of ECVET in Europe in strategic terms but also the multiplicity of purposes and perspectives attached to credit systems in VET in Europe. Implementing ECVET is not solely a matter of transparency but concerns core issues such as qualifications, provision of education and training and VET traditions and understanding. This report relates ECVET to the development of the learning outcomes approach, to validation, to education and training standards and regulations, and the development of qualifications frameworks; it also looks at changes in VET governance and the changing roles of different stakeholders, from qualifications authorities, to social partners and VET providers. It opens up potential dialogue on the role of credit systems in VET in a lifelong learning perspective." (Hrsg., BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; Europäisches Leistungspunktesystem; Lernergebnisorientierung; Europa